Agricultural policies and women food producers in Latin America and the Caribbean (IICA San JoseCR, 1994)
Presents the findings of the project Agricultural Policy Analysis vis-a-vis Women Food Producers in Latin America and the Caribbean' which was conducted in 18 countries. Provides more complete information on the Andean and Central American countries because the research has been completed in those areas; work is in the final stage in the Southern cone and in the intermediate stage in the Caribbean countries.
DC